First general report - Shortt, Edward; Nethersole, Olga, 1870-1951 (London : People's League of Health)
1922-05 1922 1920s 55 pages : illustrations MODEL TEA GOWNS In addition to the pretty and inexpensive Tea Gowns that are such a feature of this section, we have always in stock a charming variety of handsome and exclusive Tea Gowns copied and adapted from exclusive Paris Models in the richest and most fashionable materials at moderate prices [illustration] "VENUS" Handsome Tea-gown in rich black satin, which is a copy of an Original French model cut on purely classical lines. The side tunic is of sequin coat of mail, with long Grecian drapery and chiffon hanging sleeves edged sequin and tassels 25½ gns. [illustration] "ANGELA" Classical Tea-gown with wide panel back and front, of tinsel ninon brocade lined chiffon, large moyen age sleeves and side drapery of silk georgette to match. In Black-Silver, Black-Gold, Larkspur Blue-Silver, Cerise-Silver, Jade-Gold, Orchid-Silver, Grey-Silver, Emerald-Gold. Special Price 8½ gns. MARSHALL & SNELGROVE, Vere Street & Oxford Street, LONDON, W.1 (DEBENHAMS, LTD.) 200/B/3/2/C693/1/71